2011
DOI: 10.1371/journal.pone.0017714
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of the Extracellular Calcium Sensing Receptor (CaSR) in Equine Umbilical Cord Matrix Size-Sieved Stem Cells

Abstract: BackgroundThe present study investigates the effects of high external calcium concentration ([Ca2+]o) and the calcimimetic NPS R-467, a known calcium-sensing receptor (CaSR) agonist, on growth/proliferation of two equine size-sieved umbilical cord matrix mesenchymal stem cell (eUCM-MSC) lines. The involvement of CaSR on observed cell response was analyzed at both the mRNA and protein level.Methodology/Principal FindingsA large (>8 µm in diameter) and a small (<8 µm) cell line were cultured in medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…Although Barradas et al have recently shown that calcium-enhanced osteogenic differentiation in bone marrow-derived mesenchymal stromal cells is not mediated by CaSR activation [44], our results are in accordance with part of the literature in demonstrating that an elevation of Ca 2+ o concentration, as well as the use of calcimimetics, strongly activates functional CaSR in several cell lines [39], [42], [45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although Barradas et al have recently shown that calcium-enhanced osteogenic differentiation in bone marrow-derived mesenchymal stromal cells is not mediated by CaSR activation [44], our results are in accordance with part of the literature in demonstrating that an elevation of Ca 2+ o concentration, as well as the use of calcimimetics, strongly activates functional CaSR in several cell lines [39], [42], [45].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, recent works have suggested that this important receptor is expressed in stem cells such as size-sieved umbilical cord matrix equine stem cells [42], bone marrow hematopoietic stem cells [43] and mouse embryo stem cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, we suspect that the calcium sensing receptor (CaSR) may play a role in inhibiting chondrogenesis in response to increased extracellular calcium, as it has been shown to be expressed and functionally active in osteoblast-like cell lines 40 and several types of stem cells, including human and ovine amniotic fluid stem cells, 41 equine umbilical cord matrix, 42 and bone marrow mesenchymal stem cells (MSCs). 43 More recently, the calcium-sensing receptor was reported to play a potential role in the osteogenic differentiation of human amniotic fluid MSCs.…”
Section: Camentioning
confidence: 99%
“…Calcium concentration was selected on the basis of a previous study from our unit [13] in which 2.5 mM CaCl 2 was considered as CaSR EC 50 in both cell lines. External Ca 2+ concentration ([Ca 2+ ] o ) in the present study, as in our previous study by Martino et al, [13] was actually either 0.37 (low [Ca 2+ ] o ) or 2.37 mMCa 2+ (high [Ca 2+ ] o ).…”
Section: Experimental Designmentioning
confidence: 99%
“…Indeed, a recent study from our unit reported the CaSR is expressed in eUCM-MSCs and is functionally active since calcium and the selective CaSR agonist NPS R-467 stimulate cell growth/proliferation in these cell lines, an effect which is reversed by the CaSR antagonist NPS2390 [13]. On the other hand, limited information is available on the role of CaSR in cell differentiation.…”
Section: Introductionmentioning
confidence: 99%